1975
DOI: 10.1093/cvr/9.5.579
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prolonged  -adrenoceptor blockade on heart weight and cardiac intracellular potentials in rabbits

Abstract: Estimates were made in vivo in rabbits of the relative beta-receptor blocking potency and duration of action of propranolol and practolol. In further experiments groups of litter mates were injected twice daily with approximately equi-active amounts of propranolol or practolol, or with saline, for several weeks. The heart weights of the treated animals were significantly lower than those of the controls, the water contents were higher, and the dry weight differences were highly significant; -16.8% after 2 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Investigations in animals of the cellular effects of prolonged /J-blockade were begun several years ago, and it was shown that treatment of young rabbits for several weeks with /?-adrenoceptor blocking drugs at doses comparable with those used clinically had a number of secondary effects which could be distinguished from the acute actions of the drugs (Vaughan Williams et al, 1975;Raine and Vaughan Williams, 1980). Atrial transmembrane action po-tential duration was greatly prolonged, a surprising finding since, in acute experiments, /8-blockers either have no effect on action potential duration or shorten it, in both atrial (Papp and Vaughan Williams, 1969) and ventricular muscle (Davis and Temte, 1968).…”
mentioning
confidence: 99%
“…Investigations in animals of the cellular effects of prolonged /J-blockade were begun several years ago, and it was shown that treatment of young rabbits for several weeks with /?-adrenoceptor blocking drugs at doses comparable with those used clinically had a number of secondary effects which could be distinguished from the acute actions of the drugs (Vaughan Williams et al, 1975;Raine and Vaughan Williams, 1980). Atrial transmembrane action po-tential duration was greatly prolonged, a surprising finding since, in acute experiments, /8-blockers either have no effect on action potential duration or shorten it, in both atrial (Papp and Vaughan Williams, 1969) and ventricular muscle (Davis and Temte, 1968).…”
mentioning
confidence: 99%
“…One of the anti arrhythmic properties of other beta blockers may be their ability to antagonize the effects of catecholamines on automaticity and conductivity, but the effects on the ventricular repolarization are to some extent controver sial. Several beta-blocking agents with different pharma cological properties produce a moderate prolongation of the ventricular repolarization time after long-term thera py, as shown in animal studies [12,13]. The lack of an acute class III effect was recently confirmed in a study with healthy volunteers, in whom metoprolol prolonged the right ventricular repolarization time by 6-8 % after 5 weeks of treatment with 400 mg daily, while no effect could be demonstrated after acute administration [7].…”
Section: Discussionmentioning
confidence: 99%
“…Evemy et al [ 14] and Vaughan Williams et al [15] treated young rabbits with intraperito neal or subcutaneous propranolol and not ed a significantly reduced growth rate per haps related to a reduction in food intake.…”
Section: Discussionmentioning
confidence: 99%
“…young rabbits given propranolol [14,15] and in infants of mothers treated during preg nancy with long-term propranolol [16]. The present study was designed to evaluate the effect of chronic propranolol on the body growth and organ size of newborn beagle puppies.…”
Section: Introductionmentioning
confidence: 99%